Progress in Flight Dynamics, Guidance, Navigation, Control, Fault Detection, and Avionics 2013
DOI: 10.1051/eucass/201306231
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of advanced model-based fdir techniques for aerospace systems: the 2011 situation

Abstract: For aerospace systems, advanced model-based Fault Detection, Identi¦-cation, and Recovery (FDIR) challenges range from predesign and design stages for upcoming and new programs up to the improvement of the performance of in-service §ying systems. However, today, their application to real aerospace world has remained extremely limited. The paper underlines the reasons for a widening gap between the advanced scienti¦c FDIR methods being developed by the academic community and technological solutions demanded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…It is widely acknowledged by academic researchers and industrials that there is still a wide gap between state-of-the-art research in FDI and current industrial practice [34]. Within the few actually implemented schemes, diagnosis is generally part of an Integrated Vehicle Health Management (IVHM) system [314], which also includes prognosis and maintenance planning.…”
Section: Current Industrial Practicementioning
confidence: 99%
See 1 more Smart Citation
“…It is widely acknowledged by academic researchers and industrials that there is still a wide gap between state-of-the-art research in FDI and current industrial practice [34]. Within the few actually implemented schemes, diagnosis is generally part of an Integrated Vehicle Health Management (IVHM) system [314], which also includes prognosis and maintenance planning.…”
Section: Current Industrial Practicementioning
confidence: 99%
“…Emphasis will be put in this article on those modelbased quantitative methods that have been used for aerospace applications. Relatively, few books and survey papers have been published on this aspect of fault diagnosis [27][28][29][30][31][32][33][34]. The survey proposed here is supported by a large collection of references dealing with fault detection for flight systems.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent surveys, like [2] and [12], have shown that the current research priority regarding FDD consists of finding reliable solutions for the real-time implementation of technical diagnosis systems; they need to operate under very strict time constraints and support the on-line system reconfiguration and restructuring mechanisms.…”
Section: System Diagnosis Using Parameter Estimationmentioning
confidence: 99%